Theological determinism : new perspectives - Furlong, Peter; Vicens, Leigh (Cambridge : Cambridge University Press, 2022)
This volume brings together renowned scholars and emerging voices in philosophical theology and philosophy of religion to provide the most comprehensive examination of theological determinism to date, both in terms of the authors featured and the issues explored.
Introduction; 1. Theological Determinism and Creation Heath White; 2. Am I Here by Accident? T. J. Mawson; 3. You Searched Me and Knew Me: Divine Determinism and the God of Love Jesse Couenhoven; 4. Fatalism and Some Varieties of Contrastive Explanation Alexander R. Pruss; 5. Divine Transcendence: Is There a Third Way in the Debate over Theological Determinism? W. Matthews Grant; 6. The Incompatibility of Universal, Determinate Divine Action with Human Free Will Simon Kittle; 7. Compatibilists about Moral Responsibility and (Natural) Determinism Should Be Compatibilists about Moral Responsibility and Theological Determinism Taylor Cyr; 8. An Argument for Theological Incompatibilism Alicia Finch; 9. Human Freedom and the Inevitability of Sin Leigh Vicens; 10. Hard Theological Determinism and Divine Forgiveness are Incompatible Justin Capes; 11. Moral Luck, Free Will Theodicies, and Theological Determinism Philip Swenson; 12. Divine Determinism and Gratitude for Sins Peter Furlong; 13. The Problem of Trust Daniel M. Johnson; 14. Toward a Reactive Attitudes Theodicy Garrett Pendergraft; 15. Christ in Gethsemane Katherine Sonderegger.
Includes bibliographical references and index.
Keywords: Religion; Free will and determinism - Religious aspects - Christianity